Acquired non-thermal plasma resistance mediates a shift towards aerobic glycolysis and ferroptotic cell death in melanoma. (March 2023) - Lin, Abraham; Sahun, Maxime; Biscop, Eline; Verswyvel, Hanne; De Waele, Jorrit; De Backer, Joey; Theys, Claudia; Cuypers, Bart; Laukens, Kris; Berghe, Wim Vanden; Smits, Evelien; Bogaerts, Annemie
Abstract: Aims: To gain insights into the underlying mechanisms of NTP therapy sensitivity and resistance, using the first-ever NTP-resistant cell line derived from sensitive melanoma cells (A375). Methods: Melanoma cells were exposed to NTP and re-cultured for 12 consecutive weeks before evaluation against the parental control cells. Whole transcriptome sequencing analysis was performed to identify differentially expressed genes and enriched molecular pathways. Glucose uptake, extracellular lactate, media acidification, and mitochondrial respiration was analyzed to determine metabolic changes. Cell death inhibitors were used to assess the NTP-induced cell death mechanisms, and apoptosis and ferroptosis was further validated via Annexin V, Caspase 3/7, and lipid peroxidation analysis. Results: Cells continuously exposed to NTP became 10 times more resistant to NTP compared to the parental cell line of the same passage, based on their half-maximal inhibitory concentration (IC50). Sequencing and metabolic analysis indicated that NTP-resistant cells had a preference towards aerobic glycolysis, while cell death analysis revealed that NTP-resistant cells exhibited less apoptosis but were more vulnerable to lipid peroxidation and ferroptosis. Conclusions: A preference towards aerobic glycolysis and ferroptotic cell death are key physiological changes in NTP-resistance cells, which opens new avenues for further, in-depth research into other cancer types.